A silane coupling agent modification treatment method for high peel resistance, high strength and extremely low profile copper foil
Patent Information
- Application Number
- CN202611203348.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]目前行业内极低轮廓铜箔普遍存在技术问题:其一,为控制表面轮廓,铜箔表面弱化粗化处理,铜箔与树脂基材的机械咬合力大幅下降,剥离强度偏低,压合后易出现分层、脱层缺陷;其二,极低轮廓铜箔表面活性位点少,单纯采用常规硅烷偶联剂改性,偶联剂膜层附着力差、膜层不均匀,固化后易出现针孔、裂纹,无法兼顾低轮廓与高粘结性能;其三,常规硅烷改性工艺水解控制粗放,偶联剂易自聚团聚,膜层致密性差,铜箔耐氧化性能、耐湿热性能不足,长期使用易发生铜箔氧化发黑、粘结力衰减;其四,现有改性处理液配方单一,多采用单一氨基硅烷,官能团适配性差,无法同时提升铜箔机械强度与界面结合力,高温加工条件下铜箔抗拉、抗撕裂性能下降明显
本发明摒弃传统单一硅烷配方,采用氨基-环氧基-巯基三元复合硅烷体系,不同官能团协同作用,氨基基团结合铜箔表面活性位点,环氧基团适配树脂基材粘结,巯基基团强化铜晶格结合力;搭配锌锡复合纳米金属络合增强剂,构建有机-无机互穿网络结构,在不增加铜箔表面粗糙度(改性后Rz≤1.8μm)的前提下,剥离强度提升35%以上,抗拉强度提升20%,突破极低轮廓铜箔“低轮廓必低强度”的行业技术瓶颈。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of copper foil surface treatment technology, and in particular to a silane coupling agent modification treatment method for high peel resistance, high strength, and extremely low profile copper foil. Background Technology
[0002] Ultra-low profile copper foil (HVLP copper foil) is widely used in high-end electronic fields such as high-frequency and high-speed printed circuit boards, 5G communication base station materials, high-end server PCBs, and flexible copper-clad laminates due to its extremely low surface roughness, low signal transmission loss, and excellent high-frequency dielectric properties. As electronic devices rapidly evolve towards higher frequencies, thinner profiles, and higher-density integration, the market demands for the comprehensive performance of HVLP copper foil continue to increase. Not only is a surface roughness Rz ≤ 2.0 μm required, but it also needs to possess high peel strength, high tensile strength, resistance to damp heat aging, and resistance to chemical corrosion, making it suitable for precision lamination, etching, and welding processes.
[0003] Currently, ultra-low profile copper foil in the industry generally suffers from the following technical problems: First, in order to control the surface profile, the copper foil surface is weakened and roughened, which significantly reduces the mechanical interlocking force between the copper foil and the resin substrate, resulting in low peel strength and easy delamination and delamination defects after lamination. Second, ultra-low profile copper foil has few active sites on its surface. Simply using conventional silane coupling agents for modification results in poor adhesion and uneven film layer, which easily leads to pinholes and cracks after curing, failing to achieve both low profile and high adhesion performance. Third, conventional silane modification processes have crude hydrolysis control, making the coupling agent prone to self-aggregation and agglomeration, resulting in poor film density and insufficient oxidation resistance and damp heat resistance of the copper foil. Long-term use can easily lead to copper foil oxidation and blackening, as well as weakening of adhesion. Fourth, existing modification treatment solutions have simple formulations, mostly using single aminosilanes, which have poor functional group compatibility and cannot simultaneously improve the mechanical strength and interfacial bonding of the copper foil. Under high-temperature processing conditions, the tensile and tear resistance of the copper foil decreases significantly.
[0004] Most existing publicly available patents and technical solutions employ simple spraying and immersion modification with a single silane coupling agent. Some solutions add a single metal additive to improve adhesion, but these suffer from poor additive compatibility, uncontrollable film thickness, and a rebound in copper foil profile after modification. Other technologies use multi-layer inorganic coating composite modification, which is complex, costly, and prone to increasing copper foil surface roughness, thus compromising extremely low profile characteristics. Furthermore, traditional modification processes involve high curing temperatures, which can lead to coarse copper foil grains, reducing the copper foil's mechanical strength and failing to meet the stringent standards for high-end electronic boards.
[0005] In summary, existing ultra-low profile copper foil silane modification technologies suffer from technical defects such as the inability to synergistically achieve low profile, high strength, and high peel resistance, poor coupling agent film density, weak aging resistance, and low process adaptability. There is an urgent need to develop a creative modification method that can significantly improve the peel strength and mechanical strength of copper foil while strictly preserving the ultra-low profile, and optimize the film stability and weather resistance. Summary of the Invention
[0006] The purpose of this invention is to provide a silane coupling agent modification method for high peel resistance, high strength, and extremely low profile copper foil, in order to solve the above-mentioned technical problems.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for modifying high-peel-resistance, high-strength, and extremely low-profile copper foil with silane coupling agent, comprising the following steps: 1) The copper foil surface was sequentially cleaned and activated using alkaline degreasing solution and acidic micro-etching solution, rinsed with deionized water and then dried with nitrogen gas. 2) Immerse the copper foil in the modification treatment solution and heat it in two stages; 3) After draining the residual liquid from the impregnated copper foil, perform a three-stage gradient curing process; 4) In an inert gas atmosphere, the cured copper foil is sequentially cooled by air, dusted, cut, and wound up to obtain modified copper foil; The modified treatment solution is composed of a composite silane coupling agent, a metal complexing enhancer, a hydrolysis regulator, a film-forming aid, water, and ethanol.
[0008] Furthermore, in the modified treatment solution, by mass percentage, there are 1.2-2.5% composite silane coupling agent, 0.3-0.8% metal complexing enhancer, 0.15-0.4% hydrolysis regulator, 0.2-0.5% film-forming aid, and the balance is a mixed solvent of water and ethanol; wherein the mass ratio of water to ethanol is 1-2:5.
[0009] Furthermore, the preparation method of the modified treatment liquid is as follows: Heat the mixed solvent of water and ethanol to 35-40°C, add the composite silane coupling agent and hydrolysis regulator, and stir for 40-60 minutes; cool to 25-30°C, add the metal complexing enhancer and film-forming aid in sequence, stir for 20-30 minutes, and let stand to defoam.
[0010] Furthermore, the composite silane coupling agent is a mixture of aminosilane, epoxysilane and mercaptosilane, with a mass ratio of aminosilane, epoxysilane and mercaptosilane of 2~5:3:1.
[0011] Furthermore, the metal complexing enhancer is a compound of zinc acetylacetonate and tin dibutyl dilaurate, with a mass ratio of zinc acetylacetonate to tin dibutyl dilaurate of 2 to 5:1, and the particle size of the metal complexing enhancer is controlled at 20 to 50 nm. The hydrolysis regulator is a compound buffer system of glacial acetic acid and triethanolamine, with a mass ratio of glacial acetic acid to triethanolamine of 1~5:1, and the pH of the modified treatment solution is adjusted to 4.5~5.5.
[0012] Furthermore, the film-forming aid is a compound of hydroxyethyl cellulose and polyethylene glycol 400, with a mass ratio of hydroxyethyl cellulose to polyethylene glycol 400 of 1~2:1.
[0013] Furthermore, the two-stage heating and impregnation process is as follows: the first stage is impregnation at 28~32℃ for 15~25s, and the second stage is impregnation at 38~42℃ for 30~50s, with the impregnation process supplemented by low-frequency ultrasonic vibration at 25~35kHz.
[0014] Furthermore, the three-stage gradient curing process is as follows: first, pre-curing at 60~70℃ for 10~15 min, then cross-linking curing at 90~105℃ for 20~30 min, and finally stabilization treatment at 110~120℃ for 8~12 min.
[0015] Furthermore, in step 1), the thickness of the copper foil is 12~35μm, and the surface roughness Rz=1.0~1.8μm.
[0016] Furthermore, the alkaline degreasing solution is a mixed aqueous solution of sodium carbonate, trisodium phosphate, and nonionic surfactant, with a mass concentration of 5-8%, a degreasing temperature of 45-50℃, and a degreasing time of 3-5 min; the acidic micro-etching solution is a mixed solution of dilute sulfuric acid and sodium persulfate, with a hydrogen ion concentration of 0.8-1.2 mol / L, a micro-etching time of 1-2 min, and a micro-etching corrosion amount ≤0.5 μm.
[0017] The beneficial effects of this invention are: This invention abandons the traditional single silane formulation and adopts an amino-epoxy-thiol ternary composite silane system. Different functional groups work synergistically: the amino groups bind to the active sites on the copper foil surface, the epoxy groups adapt to the resin substrate for bonding, and the thiol groups strengthen the copper lattice bonding force. Combined with a zinc-tin composite nano-metal complexing enhancer, an organic-inorganic interpenetrating network structure is constructed. Without increasing the surface roughness of the copper foil (Rz≤1.8μm after modification), the peel strength is increased by more than 35% and the tensile strength is increased by 20%, breaking through the industry technical bottleneck of "low profile inevitably means low strength" for ultra-low profile copper foil.
[0018] This invention pioneers a combined process of gradient hydrolysis, two-stage impregnation, and three-stage gradient curing, which differs from conventional one-time hydrolysis and high-temperature curing processes. A weak acid buffer system precisely controls the silane hydrolysis rate, preventing coupling agent agglomeration and precipitation. Two-stage impregnation achieves layered adsorption and cross-linking, and ultrasonic assistance eliminates bubbles in the film layer. Gradient low-temperature curing gradually releases the internal stress of the film layer, avoiding copper foil grain deterioration caused by high temperatures. The film thickness is uniformly controlled at 80~150nm, dense and free of pinholes, and its resistance to damp heat aging is greatly improved.
[0019] The modification process of this invention does not require complex coating equipment and can be completed using a conventional copper foil surface treatment production line. The process has low energy consumption and easy waste liquid treatment. The modified copper foil is compatible with various substrates such as epoxy resin and polyimide, and is suitable for multiple fields such as high-frequency and high-speed PCBs, flexible circuit boards, and lithium battery current collectors. During the processing, it is not easy to have problems such as delamination, breakage, oxidation and blackening, and the product yield rate is increased to over 99%.
[0020] The modified copper foil of this invention forms a hydrophobic and dense protective film on its surface. No corrosion spots are observed after ≥72 hours of salt spray testing, and the peel strength attenuation rate is ≤8% after 2000 hours of damp heat aging testing (85℃, 85%RH), which is far superior to the industry standard and can meet the long-term and stringent service requirements of high-end electronic components. Detailed Implementation
[0021] This invention provides a method for modifying high-peel-resistance, high-strength, and extremely low-profile copper foil with silane coupling agent, comprising the following steps: 1) The copper foil surface was sequentially cleaned and activated using alkaline degreasing solution and acidic micro-etching solution, rinsed with deionized water and then dried with nitrogen gas. 2) Immerse the copper foil in the modification treatment solution and heat it in two stages; 3) After draining the residual liquid from the impregnated copper foil, perform a three-stage gradient curing process; 4) In an inert gas atmosphere, the cured copper foil is sequentially cooled by air, dusted, cut, and wound up to obtain modified copper foil; The modified treatment solution is composed of a composite silane coupling agent, a metal complexing enhancer, a hydrolysis regulator, a film-forming aid, water, and ethanol.
[0022] In this invention, the modified treatment liquid contains, by mass percentage, 1.2-2.5% composite silane coupling agent, 0.3-0.8% metal complexing enhancer, 0.15-0.4% hydrolysis regulator, 0.2-0.5% film-forming aid, and the balance is a mixed solvent of water and ethanol; wherein the mass ratio of water to ethanol is 1-2:5, preferably 2:5.
[0023] In this invention, the content of the composite silane coupling agent is preferably 1.5-2.0% by mass percentage, and more preferably 1.8-1.9%.
[0024] In this invention, the content of the metal complexing enhancer is preferably 0.4-0.7% by mass percentage, more preferably 0.5-0.6%.
[0025] In this invention, the content of the hydrolysis regulator is preferably 0.2-0.35% by mass percentage, more preferably 0.25-0.3%.
[0026] In this invention, the content of the film-forming aid is preferably 0.3 to 0.4% by mass percentage.
[0027] In this invention, the preparation method of the modified treatment liquid is as follows: Heat the mixed solvent of water and ethanol to 35-40°C, add the composite silane coupling agent and hydrolysis regulator, and stir for 40-60 minutes; cool to 25-30°C, add the metal complexing enhancer and film-forming aid in sequence, stir for 20-30 minutes, and let stand to defoam.
[0028] In this invention, the composite silane coupling agent is a mixture of aminosilane, epoxysilane and mercaptosilane, wherein the mass ratio of aminosilane, epoxysilane and mercaptosilane is 2~5:3:1, preferably 3~4:3:1; wherein the aminosilane is γ-aminopropyltriethoxysilane, the epoxysilane is γ-glycidoxypropyltrimethoxysilane, and the mercaptosilane is 3-mercaptopropyltrimethoxysilane.
[0029] In this invention, the metal complexing enhancer is a compound of zinc acetylacetonate and tin dibutyl dilaurate, wherein the mass ratio of zinc acetylacetonate to tin dibutyl dilaurate is 2~5:1, preferably 3~4:1; the particle size of the metal complexing enhancer is controlled at 20~50nm, which is used to construct an organic-inorganic complex crosslinking structure and improve the film bonding strength. The hydrolysis regulator is a compound buffer system of glacial acetic acid and triethanolamine, with a mass ratio of glacial acetic acid to triethanolamine of 1~5:1, preferably 3:1; the pH of the modified treatment solution is adjusted to 4.5~5.5, preferably 5.0, to inhibit silane self-polymerization and achieve slow and controllable hydrolysis.
[0030] In this invention, the film-forming aid is a compound of hydroxyethyl cellulose and polyethylene glycol 400, with a mass ratio of hydroxyethyl cellulose to polyethylene glycol 400 of 1 to 2:1, preferably 2:1, which improves the uniformity of the film layer and avoids pinholes and cracks in the film layer.
[0031] In this invention, the two-stage heating and immersion process is as follows: the first stage is immersion at 28~32℃ for 15~25s, and the second stage is immersion at 38~42℃ for 30~50s, with the immersion process supplemented by low-frequency ultrasonic vibration at 25~35kHz; preferably, the first stage is immersion at 30℃ for 10s, and the second stage is immersion at 40℃ for 40s.
[0032] In this invention, the three-stage gradient curing is as follows: first, pre-curing at 60~70℃ for 10~15 min, then cross-linking and curing at 90~105℃ for 20~30 min, and finally stabilizing at 110~120℃ for 8~12 min; preferably, first, pre-curing at 62~68℃ for 10~15 min, then cross-linking and curing at 95~100℃ for 20~30 min, and finally stabilizing at 115~120℃ for 8~12 min.
[0033] In this invention, in step 1), the thickness of the copper foil is 12~35μm, preferably 15~30μm; the surface roughness Rz is 1.0~1.8μm, preferably 1.2~1.5μm.
[0034] In this invention, the alkaline degreasing solution is a mixed aqueous solution of sodium carbonate, trisodium phosphate, and nonionic surfactant, with a mass concentration of 5-8%, preferably 6-7%; the degreasing temperature is 45-50℃, and the degreasing time is 3-5 min; the acidic micro-etching solution is a mixed solution of dilute sulfuric acid and sodium persulfate, with a hydrogen ion concentration of 0.8-1.2 mol / L, preferably 1.0 mol / L; the micro-etching time is 1-2 min, and the micro-etching corrosion amount is ≤0.5 μm.
[0035] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0036] Example 1
[0037] A method for modifying high-peel-resistance, high-strength, and extremely low-profile copper foil with silane coupling agent, comprising the following steps: 1) Select an electrolytic ultra-low profile copper foil with a thickness of 18μm and a surface roughness Rz=1.5μm; use a 6% alkaline degreasing solution (mass ratio: sodium carbonate: trisodium phosphate: nonionic surfactant = 5:3:2) to degrease at 48℃ for 4 min; then use a 1.0mol / L dilute sulfuric acid-sodium persulfate micro-etching solution to micro-etch for 1.5 min, rinse with deionized water, and blow dry with nitrogen; 2) By mass percentage, the composite silane coupling agent is 2.0% (mass ratio: aminosilane:epoxysilane:mercaptosilane = 5:3:1), the metal complexing enhancer is 0.5% (mass ratio: zinc acetylacetone: dibutyltin dilaurate = 4:1), the hydrolysis regulator is 0.25% (mass ratio: glacial acetic acid:triethanolamine = 3:1), the film-forming aid is 0.35% (mass ratio: hydroxyethyl cellulose:polyethylene glycol 400 = 2:1), and the balance is a mixed solvent of deionized water and anhydrous ethanol (mass ratio 2:5). Preparation of modified treatment solution: The mixed solvent is heated to 38℃, the composite silane coupling agent is slowly added dropwise, the mixture is stirred at 280r / min, the hydrolysis regulator is added and hydrolyzed at a constant temperature for 50min; the temperature is lowered to 28℃, the metal complexation enhancer and film-forming aid are added, the mixture is stirred for 25min, the mixture is allowed to stand for 15min to defoam, and the pH value is adjusted to 5.0. 3) Immerse the treated copper foil in the modification solution. The first stage is immersion at 30°C for 20 seconds, and the second stage is immersion at 40°C for 40 seconds. The ultrasonic oscillation frequency is 30kHz. 4) The impregnated copper foil is cured in sections: pre-cured at 65℃ for 12 min, cross-linked cured at 100℃ for 25 min, and stabilized at 115℃ for 10 min; then cooled by nitrogen air at a rate of 4℃ / min, and then cut and wound to obtain modified copper foil.
[0038] Example 2
[0039] In this embodiment, the raw material ratio and process parameters are adjusted as follows: 1.5% composite silane coupling agent, 0.4% metal complexing reinforcing agent, first stage impregnation temperature 29°C, time 18s, second stage impregnation temperature 39°C, time 35s; the remaining steps are completely consistent with those in Example 1.
[0040] Example 3
[0041] A method for modifying high-peel-resistance, high-strength, and extremely low-profile copper foil with silane coupling agent, comprising the following steps: 1) Select an electrolytic ultra-low profile copper foil with a thickness of 18μm and a surface roughness Rz=1.5μm; use a 6% alkaline degreasing solution (sodium carbonate: trisodium phosphate: nonionic surfactant = 5:3:2) to degrease for 4 min at 48℃; then use a 1.0mol / L dilute sulfuric acid-sodium persulfate micro-etching solution to micro-etch for 1.5 min, rinse with deionized water, and blow dry with nitrogen; 2) By mass percentage, the composite silane coupling agent is 2.5% (aminosilane:epoxysilane:mercaptosilane = 5:3:1), the metal complexing enhancer is 0.8% (zinc acetylacetone: dibutyltin dilaurate = 4:1), the hydrolysis regulator is 0.4% (glacial acetic acid: triethanolamine = 3:1), the film-forming aid is 0.5% (hydroxyethyl cellulose: polyethylene glycol 400 = 2:1), and the balance is a mixed solvent of deionized water and anhydrous ethanol (mass ratio 2:5). Preparation of modified treatment solution: The mixed solvent is heated to 40℃, the composite silane coupling agent is slowly added dropwise, the mixture is stirred at 280r / min, the hydrolysis regulator is added and hydrolyzed at a constant temperature for 60min; the temperature is lowered to 30℃, the metal complexation enhancer and film-forming aid are added, the mixture is stirred for 30min, the mixture is allowed to stand for 15min to defoam, and the pH value is adjusted to 5.2. 3) Immerse the treated copper foil in the modification solution. The first stage is immersion at 32°C for 25 seconds, and the second stage is immersion at 42°C for 50 seconds. The ultrasonic oscillation frequency is 35kHz. 4) The impregnated copper foil is cured in sections: pre-cured at 70℃ for 15 min, cross-linked cured at 105℃ for 30 min, and stabilized at 120℃ for 12 min; then cooled by nitrogen air at a rate of 4℃ / min, and then cut and wound to obtain modified copper foil.
[0042] Example 4
[0043] A method for modifying high-peel-resistance, high-strength, and extremely low-profile copper foil with silane coupling agent, comprising the following steps: 1) Select an electrolytic ultra-low profile copper foil with a thickness of 12μm and a surface roughness Rz=1.2μm; use a 5% alkaline degreasing solution (sodium carbonate: trisodium phosphate: nonionic surfactant = 5:3:2) to degrease for 3 min at 45℃; then use a 0.8mol / L dilute sulfuric acid-sodium persulfate micro-etching solution to micro-etch for 1 min, rinse with deionized water, and blow dry with nitrogen; 2) By mass percentage, the composite silane coupling agent is 1.2% (aminosilane:epoxysilane:mercaptosilane = 5:3:1), the metal complexing enhancer is 0.3% (zinc acetylacetone: dibutyltin dilaurate = 4:1), the hydrolysis regulator is 0.15% (glacial acetic acid: triethanolamine = 3:1), the film-forming aid is 0.2% (hydroxyethyl cellulose: polyethylene glycol 400 = 2:1), and the balance is a mixed solvent of deionized water and anhydrous ethanol (mass ratio 2:5). Preparation of modified treatment solution: The mixed solvent is heated to 35℃, the composite silane coupling agent is slowly added dropwise, the mixture is stirred at 250r / min, the hydrolysis regulator is added and hydrolyzed at a constant temperature for 40min; the temperature is lowered to 25℃, the metal complexation enhancer and film-forming aid are added, the mixture is stirred for 20min, the mixture is allowed to stand for 15min to defoam, and the pH value is adjusted to 4.8. 3) Immerse the treated copper foil in the modification solution. The first stage is immersion at 28°C for 15 seconds, and the second stage is immersion at 38°C for 30 seconds. The ultrasonic oscillation frequency is 25kHz. 4) The impregnated copper foil is cured in sections: pre-cured at 60℃ for 10 min, cross-linked cured at 90℃ for 20 min, and stabilized at 110℃ for 8 min; then cooled by nitrogen air at a rate of 3℃ / min, and then cut and wound to obtain modified copper foil.
[0044] Comparative Example 1
[0045] A single aminosilane coupling agent with a concentration of 2.0% was used. The mixture was hydrolyzed at room temperature in one step, directly impregnated for 40 seconds, and then cured at 130°C for 40 minutes in one step. The remaining pretreatment and posttreatment processes were the same as in Example 1.
[0046] Comparative Example 2
[0047] The metal complexing enhancer was removed from the modified treatment solution, and the remaining raw material ratios and process parameters were completely consistent with those in Example 1.
[0048] Comparative Example 3
[0049] Using the same raw material ratio as in Example 3, the gradient hydrolysis, two-stage impregnation, and gradient curing processes were eliminated. Instead, a one-time hydrolysis at room temperature, a single impregnation for 50 seconds, and a one-time curing at 125°C for 40 minutes were performed. The remaining pretreatment and post-treatment processes were the same as in Example 3.
[0050] The performance of the copper foils in each embodiment and comparative example was tested according to the national standard GB / T 5230-2023 for electrolytic copper foil. The test results are shown in the table below: Table 1
[0051] The test data shows that the modified copper foils prepared in Examples 1-4 of this invention exhibit minimal roughness increase after modification, perfectly preserving the extremely low profile characteristics. Example 3, with its high-ratio additive scheme, demonstrates the best performance, achieving a peel strength of 1.56 N / mm, a tensile strength of 292 MPa, and the best corrosion resistance and aging resistance, verifying a positive correlation between additive addition and modification effect. Example 4 is suitable for ultra-thin copper foils, with a gentle process and no issues of copper foil deformation or profile deterioration, making it suitable for the production of various specifications of extremely low profile copper foils. Comparison with Comparative Example 3 shows that after eliminating the gradient process, the performance of the copper foil under the same formulation significantly declines, proving that the combined process of gradient hydrolysis, segmented impregnation, and gradient curing in this invention has an irreplaceable synergistic effect. Furthermore, the performance of Comparative Examples 1 and 2 is far lower than that of the embodiments in this application, further confirming the innovative formulation of the ternary composite silane + metal complexation reinforcing agent and the creativity of the process, solving the technical problem of simultaneously achieving low profile, high strength, and high peel resistance in extremely low profile copper foils, making the product suitable for high-end electronic material applications in multiple scenarios.
[0052] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent, characterized in that, Includes the following steps: 1) The copper foil surface was sequentially cleaned and activated using alkaline degreasing solution and acidic micro-etching solution, rinsed with deionized water and then dried with nitrogen gas. 2) Immerse the copper foil in the modification treatment solution and heat it in two stages; 3) After draining the residual liquid from the impregnated copper foil, perform a three-stage gradient curing process; 4) In an inert gas atmosphere, the cured copper foil is sequentially cooled by air, dusted, cut, and wound up to obtain modified copper foil; The modified treatment solution is composed of a composite silane coupling agent, a metal complexing enhancer, a hydrolysis regulator, a film-forming aid, water, and ethanol.
2. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 1, characterized in that, The modified treatment solution contains, by mass percentage, 1.2-2.5% composite silane coupling agent, 0.3-0.8% metal complexing enhancer, 0.15-0.4% hydrolysis regulator, 0.2-0.5% film-forming aid, and the balance is a mixed solvent of water and ethanol; wherein the mass ratio of water to ethanol is 1-2:
5.
3. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 1 or 2, characterized in that, The preparation method of the modified treatment solution is as follows: Heat the mixed solvent of water and ethanol to 35-40°C, add the composite silane coupling agent and hydrolysis regulator, and stir for 40-60 minutes; cool to 25-30°C, add the metal complexing enhancer and film-forming aid in sequence, stir for 20-30 minutes, and let stand to defoam.
4. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 3, characterized in that, The composite silane coupling agent is a mixture of aminosilane, epoxysilane and mercaptosilane, with a mass ratio of aminosilane, epoxysilane and mercaptosilane of 2~5:3:
1.
5. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 3, characterized in that, The metal complexing enhancer is a compound of zinc acetylacetonate and tin dibutyl dilaurate, with a mass ratio of zinc acetylacetonate to tin dibutyl dilaurate of 2~5:1, and the particle size of the metal complexing enhancer is controlled at 20~50nm. The hydrolysis regulator is a compound buffer system of glacial acetic acid and triethanolamine, with a mass ratio of glacial acetic acid to triethanolamine of 1~5:1, and the pH of the modified treatment solution is adjusted to 4.5~5.
5.
6. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 3, characterized in that, The film-forming aid is a compound of hydroxyethyl cellulose and polyethylene glycol 400, with a mass ratio of hydroxyethyl cellulose to polyethylene glycol 400 of 1~2:
1.
7. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 1, 4, or 6, characterized in that, The two-stage heating and immersion process is as follows: the first stage is immersion at 28~32℃ for 15~25s, and the second stage is immersion at 38~42℃ for 30~50s. The immersion process is supplemented by low-frequency ultrasonic vibration at 25~35kHz.
8. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 7, characterized in that, The three-stage gradient curing process is as follows: first, pre-curing at 60~70℃ for 10~15 min, then cross-linking curing at 90~105℃ for 20~30 min, and finally stabilization treatment at 110~120℃ for 8~12 min.
9. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 1, characterized in that, In step 1), the thickness of the copper foil is 12~35μm and the surface roughness Rz=1.0~1.8μm.
10. The method for modifying high-peel-resistance, high-strength, ultra-low profile copper foil with silane coupling agent according to claim 1, characterized in that, The alkaline degreasing solution is a mixed aqueous solution of sodium carbonate, trisodium phosphate, and nonionic surfactant, with a mass concentration of 5-8%, a degreasing temperature of 45-50℃, and a degreasing time of 3-5 min; the acidic micro-etching solution is a mixed solution of dilute sulfuric acid and sodium persulfate, with a hydrogen ion concentration of 0.8-1.2 mol / L, a micro-etching time of 1-2 min, and a micro-etching corrosion amount ≤0.5 μm.